MODEL EKSPERIMENTAL LIMPASAN PERMUKAAN PADA PERKERASAN PAVING BLOCK DENGAN PENAMBAHAN RUMPUT ANTAR PAVING - I D G Jaya Negara; Ni Kadek Asri R W; I Wayan Yasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
The use of pavement is increasing as an impact of urban development. The pavement of the land surface is very influential on increasing surface runoff. The surface runoff will cause flooding and inundation if the drainage system is not good. The use of pavement that can reduce runoff is needed, to reduce the occurrence of floods. This study aims to determine the effect of the land surface on the value of the surface runoff coefficient (C). The material used is in the form of paving blocks with the fill of grass between paving blocks. This research was conducted using a rainfall simulator. The material used is brick-shaped paving blocks of size 20 x 10 x 8 cm with a variety of brick stacking patterns and woven mats combined with mini elephant grass with a mix ratio of 75%: 25%. The measurement results are rainfall intensity, runoff volume, and surface runoff coefficient (C). The results showed that the addition of mini elephant grass had an influence on the value of the runoff coefficient. In paving blocks without the fill of mini elephant grass has a greater coefficient. The runoff coefficients produced include: soil runoff coefficient values ranging from 0.39 - 0.44, paving blocks for brick stacking runoff coefficients range from 0.42 - 0.46, paving blocks woven mat ranges from 0.41 - 0.45, paving blocks brick stacking patterns with the fill of mini elephant grass runoff coefficient ranging from 0.40 to 0.45, and paving block woven mat patterns with of mini elephant grass runoff coefficient ranging from 0.36 - 0.41.